Caring Behavior of Undergraduate Nursing Students in Clinical Practice During COVID-19 Pandemic - Natalia Elisa Rakinaung (NUTRIX, 2023)
The Covid-19 Pandemic provides its own limitations with health protocols and this can reduce the quality of caring behavior in patient care. The aim of this study is to explore caring behavior of undergraduate nursing student in their clinical practice during Covid-19 Pandemic. This observational study was conducted to 109 Undergraduate Students with purposive sampling technique in 2-4 years. The Caring Behaviors Inventory-24 (CBI-24) questionnaire was administered to respondents in this study. The data were analyzed use descriptive analysis by SPSS version 26. Caring behavior of student in clinical practice during Covid-19 pandemic shown that CBI-24 dimensions “doing with competence” attained the highest scores among the student in third and fourth years. Dimensions of “Being With” obtained the highest scores among the second-year students. However, the nursing school still have to improve the awareness of student in responding to patients needs and providing effective service to patients. Keywords: Behaviors, Caring, Nursing, Student Abstrak Masa pandemic Covid-19 memberikan keterbatasan tersendiri dalam pelaksanaan asuhan keperawatan, sehingga hal ini dapat menurunkan kualitas perilaku caring mahasiswa dalam memberikan layanan keperawatan kepada pasien. Tujuan dari penelitian ini adalah untuk mengetahui gambaran perilaku caring mahasiswa S-1 Keperawatan dalam praktek klinik selama masa pandemi Covid-19. Penelitian observasional ini dilakukan pada 109 mahasiswa dengan teknik pengambilan sampel, purposive sampling pada mahasiswa tahun ke 2-4. Pengumpulan data menggunakan Kuesioner Caring Behaviors Inventory-24 (CBI-24). Data penelitian ini dianalisis menggunakan analisis deskriptif dengan SPSS versi 26. Hasil analisis data menunjukkan bahwa dimensi “doing with competence” memperoleh nilai tertinggi pada mahasiswa tahun ketiga dan keempat. Dimensi “Being With” memperoleh nilai tertinggi pada mahasiswa tahun kedua. Pendidikan keperawatan harus meningkatkan kesadaran mahasiswa dalam menanggapi kebutuhan pasien dan memberikan layanan keperawatan yang efektif pada pasien. Kata Kunci: Caring, Keperawatan, Perilaku, Mahasiswa